Analisis Penggunaan Bahasa Pada Lirik Lagu “BUKTI” Karya Virgoun Sebagai Bentuk Ekspresi Dan Komunikasi Emosional - Nasywa Nur Hanifah; Dellia Candra Aprilia (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2025)
This study examines the use of language in the lyrics of "Bukti" by Virgoun as a means of expressing and communicating emotions deeply. Applying Ferdinand de Saussure's semiotic theory, the research focuses on how linguistic elements such as metaphor, simile, and personification are employed to respond to and depict emotional experiences related to themes of love and devotion. Document analysis method was employed to investigate the structure and meaning content in the song lyrics, identifying emerging themes and the complex relationships among textual elements. Findings reveal that "Bukti" not only conveys profound messages about the complexities of human emotions in romantic relationships but also presents meanings that resonate deeply with listeners through simple yet nuanced language. The implications of this study significantly enrich our understanding of the role of music as a powerful medium for expressing and communicating the essence of human emotions universally. This research contributes to deepening insights into the language in song lyrics as a form of artistic expression that influences and enriches human experiences broadly.